Pengaruh kompetensi dan motivasi kerja terhadap kinerja pustakawan di Perpustakaan Kabupaten Badung - Haryanti, Ni Putu Premierita; Suhartika, I Putu (Perpustakaan Universitas Gadjah Mada, 2020)
Introduction. This paper focuses on competence, motivation, performance and work experience of librarians in Badung Regency Library. The paper aims to examine the role of moderation work in the library. Methodology. A quantitative descriptive was applied using total sampling as the sampling technique. There were 39 librarians in this study from schools, universities and district areas. Questionnaires, observations and interviews were used as data collection methods. Data Analysis. Data analysis technique used was Moderated Regression Analysis (MRA). Results and Discussion. The results showed that working experience did not moderate positively and there was no significant relationship between competence and work motivation on librarian performance. Aspects related to competency, motivation and performance of the librarians need to be increased, particularly, English skills and academic in the field of librarianship. Conclusion. Work experience does not affect competency and work motivation on the performance of the librarians so that the library management needs to re-evaluate the competency of the librarian.